Built environment characteristics and parent active transportation are associated with active travel to school in youth age 12–15. Issue 22 (21st March 2014) - Carlson, Jordan A; Sallis, James F; Kerr, Jacqueline; Conway, Terry L; Cain, Kelli; Frank, Lawrence D; Saelens, Brian E
Abstract : Purpose: To investigate the relation of factors from multiple levels of ecological models (ie, individual, interpersonal and environmental) to active travel to/from school in an observational study of young adolescents. Methods: Participants were 294 12–15-year olds living within two miles of their school. Demographic, psychosocial and perceived built environment characteristics around the home were measured by survey, and objective built environment factors around home and school were assessed in Geographic Information Systems (GIS). Mixed effects multinomial regression models tested correlates of engaging in 1–4 (vs 0) and 5–10 (vs 0) active trips/week to/from school, adjusted for distance and other covariates. Results: 64% of participants reported ≥1 active trip/week to/from school. Significant correlates of occasional and/or habitual active travel to/from school included barriers (ORs=0.27 and 0.15), parent modelling of active travel (OR=3.27 for habitual), perceived street connectivity (OR=1.78 for occasional), perceived pedestrian safety around home (OR=2.04 for habitual), objective street connectivity around home (OR=0.97 for occasional), objective residential density around home (ORs=1.10 and 1.11) and objective residential density around school (OR=1.14 for habitual). Parent modelling interacted with pedestrian safety in explaining active travel to/from school. Conclusions: Results supported multilevel correlates of adolescents' active travel to school, consistent with ecological models. Correlates of occasional and habitual active travel to/from school were similar. Built environment attributes around schools, particularly residential density, should be considered when siting new schools and redeveloping neighbourhoods around existing schools.